Decomposition of inseparable nonlinear optimization problems by the multilevel hierarchical method - Tai, Nguyen Dinh; Dieu, Phan Dinh (Journal of Computer Science and Cybernetics, 2015)
For solving one class of nonlinear optimization problems of a large-scale stationary nonseparable system, composing N interacting subsystems has proposed a three-level algorithm based on a combination of the component descent method with the dual method. An approximate variant of this algorithm is established and the convergence of last under certain conditions is proved.